2019
DOI: 10.1002/anie.201900534
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Reaction of Organic Acids with SO3 at the Air–Water Interface

Abstract: The gas‐phase reaction of organic acids with SO3 has been recognized as essential in promoting aerosol‐particle formation. However, at the air–water interface, this reaction is much less understood. We performed systematic Born–Oppenheimer molecular dynamics (BOMD) simulations to study the reaction of various organic acids with SO3 on a water droplet. The results show that with the involvement of interfacial water molecules, organic acids can react with SO3 and form the ion pair of sulfuric‐carboxylic anhydrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…Thus, the gas-phase model cannot accurately describe the realistic proton-transfer process in the condensed phase. Similar phenomena have also been reported in previous studies. Thus, to better examine the stability of anhydrous 2 H -imidazolium fluorides, a condensed [DMIm]F system was constructed, and the energy barrier for the proton-transfer process was studied using the climbing image nudged elastic band (CI-NEB) method . The computational details are given in the Supporting Information.…”
supporting
confidence: 66%
“…Thus, the gas-phase model cannot accurately describe the realistic proton-transfer process in the condensed phase. Similar phenomena have also been reported in previous studies. Thus, to better examine the stability of anhydrous 2 H -imidazolium fluorides, a condensed [DMIm]F system was constructed, and the energy barrier for the proton-transfer process was studied using the climbing image nudged elastic band (CI-NEB) method . The computational details are given in the Supporting Information.…”
supporting
confidence: 66%
“…28 Furthermore, recent studies have shown that except the dominant reaction of sulfur trioxide (SO 3 ) with water vapor in the troposphere, 29 cycloaddition reaction of SO 3 to carboxylic acids is a possible formation mechanism of carboxylic sulfuric anhydrides which would have lower vapor pressure than the corresponding carboxylic acids and have more inter-molecular interaction sites. [30][31][32] It is hence speculated that the contribution of DTAA to new particle formation may be improved by the reaction with SO 3 to generate diaterpenylic acetate sulfuric anhydride (DTASA, C 10 H 16 O 9 S).…”
Section: Introductionmentioning
confidence: 99%
“…The geometries of the reactant states, transition states, and product states in all the reactions are optimized at the unrestricted M06-2X/cc-pVDZ-F 12 level, [44][45][46] which has shown good results on weak interactions and has been widely used in computational studies of atmospheric chemistry. 16,[46][47][48] Zeropoint energy (ZPE) corrections are included when calculating the potential energies, and intrinsic reaction coordinate (IRC) analysis is carried out to conrm the reaction pathways. WB97XD/cc-pVDZ-F12 and B2PLYPD/def2-TZVP methods are also employed for the total potential energy proles for comparison, which show great consistency with energy proles based on M06-2X.…”
Section: Details Of Qm Calculations and Bomd Simulationsmentioning
confidence: 99%
“…The time step of BOMD is set to 1.0 fs, which has been proven to achieve sufficient energy conservation for water systems. 34,47,58 The reaction process is unchanged with a smaller time step of 0.5 fs (ESI Fig. S7 †).…”
Section: Details Of Qm Calculations and Bomd Simulationsmentioning
confidence: 99%